The The theory of risk in the sale. : A mistake in Colombian Civil Law - García Rivera, Claudia Patricia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The Colombian Civil Code regulates the theory of risk in the contractual relationships that arise from the sale. The buyer is not the owner and bears the fortuitous loss of the thing, having to execute the payment provision knowing that the debtor will not meet theirs, in a situation that threatens the contractual balance of act. The theory is taken from French law, George Ripert (n. d) and adopted by the Colombian law. It is proposed that the cause of the contract, element of formation, and execution of the act is accepted in order to restrict the threat that puts the legal stability of the act at risk.